PENINGKATAN EKSPOR CRUDE PALM OIL (CPO) INDONESIA KE RUSIA TAHUN 2009-2013 - Wulandari, Putri; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research will explain about the increasing of Crude Palm Oil (CPO) export from Indonesia to Russia. Russia’s climate made it impossible for plants to grow. This leads to problem meeting the foods needed by the country. Therefore, Russia needs to import products from another country. This research was built by using Heckscher—Ohlin theory from mercantilism point of view. Formulation of all arguments, data, facts, and theoretical framework in this research is based on qualitative explanation and data collected method. Level of analyzed used for research is nation-state, explaining the cause of increasing export value of crude palm oil from Indonesia to Russia. This research proves that the main factor for the increase of Indonesia’s Crude Palm Oil export to Russia is because Indonesia has a good bilateral relation with Russia.Keywords: Crude Palm Oil, bilateral relation, trade, Black Campaign, Direct Trade